The comparative analysis of corporate organizational legal forms in Ukraine and EU - Tretiak, Viktoriia; Bieliai, Maksym; Третяк, В. П.; Бєляй, М. С. (Харківський національний автомобільно-дорожній університет, 2017)
Given impact of European integration processes and the growing interest of the state to enhance the corporate sector of Ukraine is topical question in the study of the current state of the corporate sector. This article provides a comparison of some fundamental indicators of the corporate sector of Ukraine and Europe in order to identify the differences and determine their causes and consequences. An objective is to develop concrete solutions to one of the urgent problems, namely to identify the causes of imperfect vision of the essence of corporate governance in Ukraine and offer modern vision of the classification of types of a business entity in their relation to the corporate sector. To achieve this goal, it is necessary to identify the causes of the problems and the consequences of their impact on the structural indicators, indexes of efficiency and utilization of the investment potential of Ukrainian enterprises. The paper contains a comparative analysis of corporate ownership of Ukraine and the EU, matching their structural indicators of economic activity and profitability compared to the analyzed systems. The study found significant differences in understanding the types of business entity that should be attributed to the corporate sector, and which have only signs of and lack of legislative framework. It was discovered that about 96% of corporate en terprises in Ukraine in the understanding of Europe cannot be attributed to the corporate sector, making it impossible to compare the state of corporate governance Ukraine and the EU. Comparing profitability, it was found that ¾ enterprises COP Ukraine is profitable but the total damage more than twice higher than the income. While profitability in the EU crisis years does not decrease below 30%. A comparison of structural indicators of economic activity revealed that economic targets both corporate sectors. At a time when European corporations are more focused on the production of high-end products and information, Ukrainian quarter engaged in the production of raw materials that inherently has low profitability. This is caused by large amounts of damage in industry and agriculture. The elements of scientific novelty and value of work must include the results of comparative analysis of corporate types of business entity in Ukraine and the EU, analysis and identification of the reasons of outlined problems and proposed alternative classification types of business entity with clear guidelines for its implementation and legislative framework. This classification distinguishes the Ukrainian enterprises as those that refer to corporate enterprises, en terprises with corporate features and non-corporate enterprises. The perspectives of further development of the outlined topics include the following vectors. Firstly, further search of the differences and problems of the corporate sector in Ukraine. Secondly, to find ways and methods to resolve identified problems with European experience. Thirdly, it is necessary to develop practical schemes and algorithms in order to bring the Ukrainian corporate sector to the competitive position and to prepare its effective integration into European space.
Порівняльний аналіз корпоративних організаційно-правових форм господарювання України та ЄС
Keywords: corporate sector; corporations; corporate organizational - legal forms; corporate governance; the European corporate sector; corporate sector in Ukraine; FDI; joint stock companies; profitability; economic activities; корпоративний сектор; корпорації; копоративні організаційно-правові форми; корпоративне управління; Європейський корпоративний сектор; корпоративний сектор України; прямі іноземні інвестиції; акціонерні товариства; прибутковість; види економічної діяльності; 338.001.36